On electric-pulse well drilling and breaking of solids - Kusaiynov, K.; Nussupbekov, B. R.; Shuyushbayeva, N. N.; Tanasheva, N. K.; Shaimerdenova, K. M.; Khassenov, A. K. (Pleiades Publishing, 2017)
Research work has been carried out to determine the power-efficient regime of operation of an electric-pulse setup for breaking and crushing natural stones. The optimal energy and geometrical parameters of the method (dependence of the degree of breakdown of materials on the voltage and the electrode spacing in the switching unit) have been established. The proposed method makes it possible to effectively perform drilling in vertical wells for installing heat exchangers of thermal pumps.